Tirtayatra sebagai Bentuk Wisata Religi Masyarakat Hindu di Bali - I Nengah Aryanatha (UHN IGB Sugriwa Denpasar, 2017)
Various forms of travel nowadays continue to grow, one of which is religious tourism. Religious tourism is one of the phenomenon that is currently starting to populate, it proved many activities or activities associated with religious tourism such as Tirta Yatra conducted by Hindu community in Bali. In some community groups, religious tourism is often used as a monthly, annual, and routine activities. In addition to getting the calm and pleasure (refreshing), it will also gain insight into the sacred historical sites and increase awareness of gratitude for the omnipotence of God (Ida Sang Hyang Widhi Wasa). Therefore, not only the health of mind that is obtained throughreligious tourism, but also the reward by interpreting the tour as a worship to improve or strengthen the faith.